Efficient merging of copper and photoredox catalysis for the asymmetric cross-dehydrogenative-coupling of alkynes and tetrahydroisoquinolines. Issue 2 (5th November 2014) - Perepichka, Inna; Kundu, Soumen; Hearne, Zoë; Li, Chao-Jun
Abstract : A highly efficient catalytic asymmetric alkynylation of prochiral CH2 groups in tetrahydroisoquinoline was developed using copper catalyzed cross-dehydrogenative-coupling of sp 3 and sp C–H bonds with the assistance of a photocatalyst and visible light. Abstract : A highly efficient catalytic asymmetric alkynylation of prochiral CH2 groups in tetrahydroisoquinoline was developed using copper catalyzed cross-dehydrogenative-coupling of sp 3 and sp C–H bonds with the assistance of a photocatalyst and visible light.